Attenuation of tall flexible structures using longitudinal moving mass: Moving finite element method. (October 2017) - Walker, Mario P; Okuma, Masaaki; Sakamoto, Hiraku
For the foreseeable future, tall building structures will be built taller and more flexible, which means more vulnerable to excitations. As such, there is considerable interest in developing structural control methods to protect against harmful vibrations. However, challenges present themselves for conventional mass damper systems as these tend to primarily utilise lateral motion which becomes very limited as the height of structures increases. This article proposes a novel approach to reduce tall building's long-period oscillations using mass damper motion in the much larger longitudinal direction. This motion induces Coriolis effect and if manoeuvred properly can be used to effectively reduce vibration of the primary structure. Numerical analysis was done using finite element method. The Shinjuku Mitsui Building was used as a benchmark for the primary structure, which was modelled as a vertical cantilever beam. The results showed the concept to be a viable approach for damping long-period vibrations of flexible structures. Enhancing this effect was also introduced and briefly discussed, using a multiple-degree-of-freedom damper and a constant positive velocity water-flow damper as examples. Further work continues for optimum design of the concept to make it a practical approach for tall buildings. Additionally, investigation into enhancing the damping effect is being done in more detail. This approach provides new possibilities for vibration control of any long-period structure.